2020
DOI: 10.3389/fenrg.2020.560849
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Capture From Flue Gas and the Atmosphere: A Perspective

Abstract: Climate change has become a worldwide concern with the rapid rise of the atmospheric Co2 concentration. To mitigate Co2 emissions, the research and development efforts in Co2 capture and separation both from the stationary sources with high Co2 concentrations (e.g., coal-fired power plant flue gas) and directly from the atmosphere have grown significantly. Much progress has been achieved, especially within the last twenty years. In this perspective, we first briefly review the current status of carbon capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
176
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(176 citation statements)
references
References 294 publications
(311 reference statements)
0
176
0
Order By: Relevance
“…We discuss the metabolic consequence of the different photosynthetic and respiratory responses to high or low CO 2 levels in two Chlorella genus. It worth to note that CO 2 concentration in flue gases can reach higher concentration than 3%, being usually in the 10–20% range (X. Wang & Song, 2020 ). Previous work demonstrated that increase CO 2 availability in the range of 1–8% saturated biomass productivity in C. vulgaris , while higher CO 2 concentration caused a strong reduction in biomass yield (Garcia‐Cubero et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We discuss the metabolic consequence of the different photosynthetic and respiratory responses to high or low CO 2 levels in two Chlorella genus. It worth to note that CO 2 concentration in flue gases can reach higher concentration than 3%, being usually in the 10–20% range (X. Wang & Song, 2020 ). Previous work demonstrated that increase CO 2 availability in the range of 1–8% saturated biomass productivity in C. vulgaris , while higher CO 2 concentration caused a strong reduction in biomass yield (Garcia‐Cubero et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…XGBoost (XGB): XGBoost algorithm 86 as implemented in XGBoost python module (v.1.2.0) 87 was used. The following hyperparameters were tuning during optimization (grid search): number of trees (50, 100, 300, 500), number of features (all features, 70% of all features), number of samples (all samples, 70% of all samples), the maximum depth of the tree (3,5,10), learning rate (0.3, 0.1, 0.5, 0.05), the minimum sum of instance weight needed in a node (1,5,10). All other parameters were left as default.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…academics and industry, notably in China. It is anticipated that the CO 2 concentration will reach 900-1100 ppm if we will not take immediate and major actions to reduce the CO 2 emissions (Wang and Song, 2020) and the temperature will rise 5°C by the century's end (Pachauri and Reisinger, 2007). As a result, it is necessary to reduce CO 2 emissions from stationeries especially fossil fuel power plants.…”
Section: H I G H L I G H T Smentioning
confidence: 99%